Pheochromocytoma and gastrointestinal stromal tumours in an adult neurofibromatosis type 1 patient: A rare co-occurrence - Nuttawut Vongsumran (2020)
© 2020 BMJ Publishing Group. All rights reserved. The risk of tumours including pheochromocytoma and gastrointestinal stromal tumour (GIST) has been reported to be higher in neurofibromatosis type 1 (NF1) patients. The concomitant occurrence of these two tumours was rare in NF1 patient and most were symptomatic. In this case report, we describe the case of a 47-year-old man with NF1 who presented with microscopic haematuria. Neither hypertension nor any gastrointestinal symptoms were reported by the patient. While investigating for haematuria, left adrenal mass and arterial enhancing lesions in the small bowel were incidentally documented during computerised urography. The patient subsequently underwent a left adrenalectomy and small bowel resection. The pheochromocytoma and multiple GIST tumours were diagnosed based on pathology. Here, we discuss the rare association of pheochromocytoma and GIST and the asymptomatic presentation of those tumours in an NF1 patient. We further suggest that in NF1 patients a heightened level of vigilance can help identify this infrequent combination.